Correction of Periodontal Tissue Microcirculation Disorders in Patients with Coronary Heart Disease with Post-Covid Syndrome - Kuvayev О. С.; Viderska Г. В.; Mostovyi С. Є. (Actual Dentistry, 2025)
Actuality. Coronary heart disease (CHD) remains one of the leading causes of death worldwide, significantly affecting patients’ quality of life. At the same time, the COVID-19 pandemic has introduced new challenges to cardiology practice, as the SARS-CoV-2 virus directly affects the endothelium, causing microcirculatory dysfunction. Objective: to determine the effectiveness of the proposed drug composition with arginine in the complex treatment of patients with coronary artery disease in combination with post-covid syndrome in the presence of concomitant generalized periodontitis by assessing the state of blood flow in periodontal microvessels by laser Doppler flowmetry. Material and methods. Clinical studies were conducted in 84 patients with coronary artery disease, post-COVID syndrome, and chronic generalized periodontitis. The state of the patients’ periodontal tissues before and after treatment was comprehensively examined. The Schiller-Pisarev test, PMA index C. Parma, the Green-Vermillion hygiene index, and the Kulazhenko vacuum test were used to assess the clinical effectiveness of treatment. Laser Doppler flowmetry was also used to assess the effectiveness of treatment. Results. The study found that the proposed drug composition’s inclusion in the complex therapy of patients with chronic coronary artery disease, post-COVID syndrome, and generalized periodontitis allows more effective suppression of the dystrophic-inflammatory process in periodontal tissues. A decrease in the PMA index confirms this, an increase in the time of hematoma formation during the Kulazhenko vacuum test, and an improvement in the level of oral hygiene and microcirculation in the periodontal tissues of patients. Conclusions. The proposed drug composition can increase the effectiveness of treating patients with coronary artery disease and post-COVID syndrome in combination with generalized periodontitis and improve the microcirculation in periodontal tissues.